Physical Fitness and Executive Functions in Preschool Children - Hermahayu, Hermahayu (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2019)
Neurophysiological maturity plays a crucial role for the school adjustment of preshool children. It also affects Executive Function (EF) as the ability to regulate behavior and to control children's emotions. The children? neurophysiological maturity is influenced by the physical fitness level. Children with better fitness can do better physical and psychological activity than children who are not fit. This study aims at revealing the relationship between physical fitness and EF as well as each of its components towards preschool children. It is also to measure the role of maternal education level and family income as a moderator of the relationship between physical fitness and EF in preschool children. Subjects in this study were 224 children (male = 110, female = 114) aged 60 months - 84 months in Magelang City. The results showed that physical fitness is positively influence to EF in which the more fit child will achieve better EF abilities. This study also found that maternal education level and family income were not moderators of the relationship between fitness and EF. The results of this study can have implications to raise an understanding on the benefits of physical activity and fitness for children.